Recent incidence trend of elderly patients with glioblastoma in the United States, 2000–2017 - Chen, Boran (BMC Cancer, 2021)
BACKGROUND: The incidence of glioblastoma increases significantly with age. With the growing and aging population, there is a lack of comprehensive analysis of recent glioblastoma incidence trend in the United States. This study aims to provide in-depth description of the patterns of incidence trends and to examine the age-period-cohort effects to the trends of glioblastoma specific to elderly patients. METHODS: The incidence rates were age-adjusted and reported per 100,000 population. We calculated the annual percent change (APC) in incidence using the Joinpoint Regression Program and conducted an age-period-cohort analysis of elderly glioblastoma reported between 2000 and 2017 to the Surveillance Epidemiology and End Results (SEER) 18 registry database. RESULTS: The overall incidence rate of elderly patients with glioblastoma was 13.16 per 100,000 (95% CI, 12.99–13.32) from 2000 to 2017. Non-Hispanic whites (20,406, 83.6%) made up the majority. The incidence rate of male was about 1.62 times that of female. The trend of incidence remained stable and there was a non-significant increasing tendency for all elderly patients (APC 0.3, 95% CI, − 0.1 to 0.7, p = 0.111). There was a significantly increasing incidence trend for non-Hispanic white (APC 0.6, 95% CI, 0.2 to 1.1, p = 0.013), supratentorial location (APC 0.7, 95% CI, 0.2 to 1.3, p = 0.016), tumor size < 4 cm (APC 2.5, 95% CI, 1.4 to 3.6, p < 0.001), and a significantly decreasing trend for overlapping/NOS location (APC -0.9, 95% CI, − 1.6 to − 0.2, p = 0.012), and unknown tumor size (APC -4.9, 95% CI, − 6.6 to − 3.3, p < 0.001). The age-period-cohort analysis showed the effect of age on incidence trends (p< 0.001, Wald test), while did not indicate the period and cohort effects of the incidence trends of glioblastoma (p = 0.063 and p =0.536, respectively, Wald test). CONCLUSION: The overall incidence of glioblastoma in the elderly population remained stable between 2000 and 2017. Period and cohort effects were not evident in the trend of glioblastoma incidence. Future population-based studies exploring the difference in the trend of glioblastoma incidence by specific molecular subgroups are warranted to further our understanding of the etiology of glioblastoma.